2022
DOI: 10.3390/app122110845
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance of CentionTM Alkasite Restorative Material vs. Glass Ionomer Cement Used in Deciduous Teeth: One-Year Evaluation

Abstract: Conservative dentistry in primary dentition aims to remove and repair existing carious lesions and to prevent secondary caries up until exfoliation of the primary tooth happens, in order to maintain the important role in terms of the space maintenance and guidance for eruption that deciduous teeth have. Many different materials are used, and some of them, recently commercialized, show bioactive properties able to prevent secondary caries. This trial’s primary focus is to evaluate the biological, functional, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The ability of alkasite to meet the ISO requirement for minimum FS even under such unfavorable conditions indicates its optimal mechanical stability and potential for use in load-bearing areas. This is consistent with reports of alkasite’s good performance under clinical conditions, albeit with short follow-up times of only 1–2 years [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The ability of alkasite to meet the ISO requirement for minimum FS even under such unfavorable conditions indicates its optimal mechanical stability and potential for use in load-bearing areas. This is consistent with reports of alkasite’s good performance under clinical conditions, albeit with short follow-up times of only 1–2 years [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…Some compositional differences among these material versions are likely but have not been explicitly stated by the manufacturer. Regardless of the material version, there is a reasonable amount of evidence for the good performance of the alkasite under in vitro conditions [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ], as well as in randomized clinical trials [ 13 , 14 , 15 , 16 , 17 ], as summarized below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another clinical study in pediatric dentistry compared the biological, functional, and aesthetic properties of Cention N to glass ionomer cement (GIC) for direct restorations of primary dentition. According to data from their study, both CN materials and GIC showed the same performance after one year [ 30 ]. Therefore, the present study corroborates their findings, suggesting the importance of proper curing and handling, as well as the ions’ activity, in controlling biochemical phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have been conducted to assess the clinical performance of Cention N, investigating its effectiveness in restoring Class I, Class II, and Class V preparations in permanent and deciduous teeth. 7 9 The results of these clinical trials have demonstrated that Cention N produces outcomes that are clinically acceptable in terms of retention, postoperative sensitivity, and secondary caries, comparable with those achieved usingresin composite materials. Additionally, Cention N has better clinical performance than glass ionomer cement.…”
Section: Introductionmentioning
confidence: 95%